PERFORMANCE OF A FISHERY HARVESTING DIFFERENT MINIMUM SHRIMP SIZES IN THE ARAFURA SEA - Purwanto Purwanto (Indonesian Fisheries Research Journal, 2012)
Avoiding overfishing and ensuring the sustainability of the shrimp stock in the Arafura Sea are of prime importance for fishery management. Exploited shrimp stock consists of several cohorts, and grows considerably with age. When the shrimps are caught before the cohort has had the opportunity to achieve its optimum biomass level, the fishery will lose much of the potential benefit that could be achieved by catching them in the near future. Therefore, a bio-economic approach was developed, on the basis of the length-based Thompson & Bell model, to evaluate the impact of harvesting different size of shrimps on fishery performance. The result of analysis shows that the fishery achieved the optimal total profit when the shrimp size at first-capture and fishing mortality were 29 mm CL and 0.50, respectively. The total profit to the fishery would be sub-optimal when the shrimp size at-first-capture was smaller or larger than the optimal size. Further, it was more economical to harvest shrimps at the larger size and higher fishing mortality, and resulting in higher total profit, when natural mortality decreased.